A new approach to Cas9-based genome editing in Aspergillus niger that is precise, efficient and selectable - Leynaud-Kieffer, Laure M. C.; Curran, Samuel C.; Kim, Irene; Magnuson, Jon K.; Gladden, John M.; Baker, Scott E.; Simmons, Blake A. (PloS one, 2019)
Aspergillus niger and other filamentous fungi are widely used in industry, but efficient genetic engineering of these hosts remains nascent. For example, while molecular genetic tools have been developed, including CRISPR/Cas9, facile genome engineering of A. niger remains challenging. To address these challenges, we have developed a simple Cas9-based gene targeting method that provides selectable, iterative, and ultimately marker-free generation of genomic deletions and insertions. This method leverages locus-specific "pop-out" recombination to suppress off-target integrations. We demonstrated the effectiveness of this method by targeting the phenotypic marker albA and validated it by targeting the glaA and mstC loci. After two selection steps, we observed 100% gene editing efficiency across all three loci. This method greatly reduces the effort required to engineer the A. niger genome and overcomes low Cas9 transformations efficiency by eliminating the need for extensive screening. This method represents a significant addition to the A. niger genome engineering toolbox and could be adapted for use in other organisms. It is expected that this method will impact several areas of industrial biotechnology, such as the development of new strains for the secretion of heterologous enzymes and the discovery and optimization of metabolic pathways.